Coherent and incoherent flow structures behind a normal flat plate - Mazharoglu, Ç; Hacisevki, H (Elsevier Science Inc, 1999)
By means of triple-decomposition, characteristics of coherent and incoherent contributions in the wake of a flat plate were examined in a domain x/D = 2-8 at a Reynolds number of 3.3 x 10(4). Significant lateral momentum transfer to a growing vortex was Obtained 1/3 period after a vortex was shed. Coherent and incoherent energy production was initiated at the edges of the flat plate with subsequent diffusion laterally and then in free-stream direction. Coherent shear stress [(u) over tilde<(upsilon)over tilde>]nates twice per cycle due to <(upsilon)over tilde> lagging behind (u) over tilde by 1/4 of a cycle; time mean coherent stress is zero. Although normal incoherent stresses are around 10% of U-infinity(2), peak values for [<(u'upsilon')over bar>] are at most 3% or lower. (C) 1999 Elsevier Science Inc. All rights reserved.
Keywords: coherent; incoherent; phase averaging